1992
DOI: 10.1007/bf01296570
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ultrastructure of hepatocytes and liver test results before, during, and after treatment with interferon-? in patients with HBeAg-positive chronic active hepatitis

Abstract: We studied the histological and ultrastructural changes in the liver and alterations in the liver test results before, during, and after treatment with human interferon-beta from five patients with hepatitis B e antigen-positive chronic active hepatitis. A daily dose of 3 x 10(6) to 6 x 10(6) units of interferon-beta was given intravenously for four weeks. The total index of periportal and portal inflammation, intralobular degeneration, and focal necrosis before treatment was decreased significantly six months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Itoh et al (11) showed the ultrastructural change of hepatocytes in patients receiving interferon for chronic hepatitis B. A marked decrease in the number of mitochondria, as well as alterations of endoplasmic reticulum and fat vacuoles, were seen in their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Itoh et al (11) showed the ultrastructural change of hepatocytes in patients receiving interferon for chronic hepatitis B. A marked decrease in the number of mitochondria, as well as alterations of endoplasmic reticulum and fat vacuoles, were seen in their patients.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 commercially available interferon beta products are recombinant, parenterally administered polypeptides. Interferon beta-1a has direct effects on hepatocytes acting through cell surface receptors and leading to changes in gene expression and protein synthesis and hepatocyte ultrastructure (31). Interferon beta can depress the activity of inducible and constitutive cytochrome P-450 isoenzymes that may alter the metabolism of other drugs (3233).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-a also decreases the transcription of mitochondrial DNA and could thereby impair fatty acid p oxidation (9). Indeed, in patients treated with IFN-a for chronic hepatitis B, ultrastructural modifications of the liver, including fat vacuoles, suggesting decreased fatty acid oxidation have been reported (10). However, this mechanism remains hypothetical in the case of our patient, as microvesicular steatosis, a characteristic lesion when fatty acid p oxidation is inhibited (1 l), was not evidenced on both liver specimens.…”
Section: Numerous Adverse Effects Have Been Reported Withmentioning
confidence: 99%